AKTIVITAS MARKETING PUBLIC RELATIONS PADA L’CHEESE FACTORY UNTUK MEWUJUDKAN THE BEST LOCAL BRAND DI PEKANBARU - Mutia Asfarina; Tantri Puspita Yazid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Nowadays dessert cafe has been a trend and also a life style of Pekanbaru society. It can be seen from the rising of many dessert caffe and accompanied by many people who spend most of their times there. L’Cheese Factory is the first local brand dessert café in Pekanbaru. Started out as kind of Small Medium Enterprises (UKM) and then keep evolve until be a corporate just like today. L’Cheese Factory got an award on UMKM award 2013 as a Inspiring Local Brand, and in 2015 got an award too as Marketeers of the year. This research aims to find out and describe about marketing public relations activity on L’Cheese Factory to actualize the best local brand in Pekanbaru.This research using qualitative research method with descriptive approach and supported with S-O-R as grounded theory, meanwhile research’s focus referred to marketing public relations concept. The subject of this research was choosing by purposive sampling technique who consists of owner, general manager, brand manager, 2 employees and 4 loyal customers of L’Cheese Factory. Data was collected through interview, observation and documentation, Data was analyst using Interactive model of Miles & Huberman. To achieve the validity of the data in this study, researcher used the triangulation technique.The results showed publication activity of L’cheese Factory commonly affiliated with publication about the held of an event. Media that used on publication activity are online media as the main media and supported by the other internal media. While the publicity activity including publicity on television, radio, and newspaper. Furthermore event consists of Sketch Walk Competition, Garnish Class, Internship Program, and Cat Rescue. Community involvement is actualized with giving support to Ikatan Bujang Dara Kota Pekanbaru community and humanitarian aid community. Inform or image is actualized with notice the quality of product, increasing service, inform company’s achievement and making merchandise. Next lobby and negotiation activity aims to some companies such Riau Kepri Bank, Mandiri Prioritas Bank, Garuda Indonesia and Awal Bros Pekanbaru Hospital.Key Words: Marketing Public Relations Activity, PR Mix, S-O-R, The Best Local Brand.